Pengembangan Video Tutorial Penataan Modifikasi Hijab Pengantin Akad Nikah - Fatimah Nabila; Jenny Sista Siregar; Aniesa Puspa Arum (Departement of Mathematics Education, 2024)
Limited time and learning media in bridal hijab styling material in the Cosmetology Education Study Program creates difficulties in the learning process. From the results of the needs analysis, 100% of respondents agreed that a video tutorial on how to modify the bridal hijab for their wedding ceremony was carried out. This research focuses on developing learning media, namely by producing video tutorials which makes this research included in the Research and Development (R&D) type of research using the ADDIE development model, but is limited to the development stage. The aim of this research is to develop video tutorials so that they can serve as information and references for students and the general public to improve their skills in arranging bridal hijab modifications. The data analysis technique uses a mix method, namely data collection and analysis is carried out using quantitative and qualitative research. This development research was carried out through a validation test process by material experts and media experts, as well as student practicality tests. In the material expert assessment I at stage I it was 67.69% and at stage II it was 86.15%. Then, the results of the material expert validation test II were 96.92% so it was included in the